Purulent Hidradenitis. Part I - A. N. Rodionov; S. V. Skrek; A. V. Sobolev; A. A. Yunovidova; L. R. Chernova; P. Wolkenstein (Vestnik Dermatologii i Venerologii, 2018)
Until recently, the pathogenesis of purulent hidradenitis was a little- and sporadically studied issue, which invariably created difficulties in the therapeutic treatment of this disease. Its often severe recurrency rate, high incidence and the lack of effective treatment have predetermined the urgency of the problem and raised the scientific and practical interest in this field among the scientists worldwide. Recent data indicate a significant role of damage-associated molecular patterns (DAMP) and the activation of congenital immunity, associated with Th17 lymphocytes, in the development of inflammatory disease. Likewise, the violation of the transmission of the cellular Notch signaling pathway plays an important role in the development of purulent hidradenitis.